Application of Response Surface Methodology to Optimize Alkali Concentration, Corn Stover Particle Size, and Extruder Parameters for Maximum Sugar Recovery - Karunanithy, Chinnadurai; Muthukumarappan, Kasiviswanathan (IntechOpen, 2011)
None